Species‐specific susceptibility to cannabis‐induced convulsions. (25th March 2018) - Whalley, Benjamin J; Lin, Hong; Bell, Lynne; Hill, Thomas; Patel, Amesha; Gray, Roy A; Elizabeth Roberts, C; Devinsky, Orrin; Bazelot, Michael; Williams, Claire M; Stephens, Gary J
Abstract : Background and Purpose: Numerous claims are made for cannabis' therapeutic utility upon human seizures, but concerns persist about risks. A potential confounder is the presence of both Δ 9 ‐tetrahydrocannabinol (THC), variously reported to be pro‐ and anticonvulsant, and cannabidiol (CBD), widely confirmed as anticonvulsant. Therefore, we investigated effects of prolonged exposure to different THC/CBD cannabis extracts on seizure activity and associated measures of endocannabinoid (eCB) system signalling. Experimental Approach: Cannabis extract effects on in vivo neurological and behavioural responses, and on bioanalyte levels, were measured in rats and dogs. Extract effects on seizure activity were measured using electroencephalography telemetry in rats. eCB signalling was also investigated using radioligand binding in cannabis extract‐treated rats and treatment‐naïve rat, mouse, chicken, dog and human tissue. Key Results: Prolonged exposure to cannabis extracts caused spontaneous, generalized seizures, subserved by epileptiform discharges in rats, but not dogs, and produced higher THC, but lower 11‐hydroxy‐THC (11‐OH‐THC) and CBD, plasma concentrations in rats versus dogs. In the same rats, prolonged exposure to cannabis also impaired cannabinoid type 1 receptor (CB1 receptor )‐mediated signalling. Profiling CB1 receptor expression, basal activity, extent of activation and sensitivity to THC suggested interspecies differences in eCB signalling, being more pronounced in a species that exhibited cannabis extract‐induced seizures (rat) than one that did not (dog). Conclusions and Implications: Sustained cannabis extract treatment caused differential seizure, behavioural and bioanalyte levels between rats and dogs. Supporting radioligand binding data suggest species differences in eCB signalling. Interspecies variations may have important implications for predicting cannabis‐induced convulsions from animal models. Linked Articles: This article is part of a themed section on 8 th European Workshop on Cannabinoid Research. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.10/issuetoc